IMPACT OF TIMELY ANTIMICROBIAL THERAPY FOR URINARY TRACT INFECTIONS ON PREECLAMPSIA: A PROSPECTIVE OBSERVATIONAL STUDY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Preeclampsia (PE) is one of the most significant complications of pregnancy, associated with a high risk of maternal and perinatal morbidity and mortality. According to current data, PE develops in 2–8% of pregnant women and remains one of the leading causes of antenatal hospitalization, preterm birth, and obstetric interventions. Of particular interest is the comparison between expectant management and prophylactic treatment, especially when paucisymptomatic forms of UTI are detected in the first or second trimesters.